ERANCANGAN PROTOTYPE KENDALI LAMPU BERBASIS INTERNET OF THINGS (IOT) DENGAN NODEMCU ESP8266 DAN VOICE RECOGNITION PADA SMARTPHONE - Yus Jayusman; Irfan Faisal; Rahmat Zaneal (LPPM STMIK BANDUNG, 2020)
Manufacture of prototype of light control was used for simplicity in turning on or turning off the lights, because basically people like something more practical and easy. In the making of this prototype, hope that can make easy of turning on and turning off the lights without switching directly from the switch. This Light Control system is based on Internet of Things (IoT) and using NodeMCU ESP8266 as the mocrocontroller and an Android App as a control gate of the system. This tool utilize voice recognition of Google to receive voice commands and translated to a form of command line for turning on or turning off the lights wirelessly. Software development methodology uses the prototype method with system design using UML. NodeMCU ESP8266 is used as the core control system.